Regulatory B Cells in Pregnancy: Lessons from Autoimmunity, Graft Tolerance, and Cancer - Guzman-Genuino, Ruth Marian; Diener, Kerrilyn R. (Frontiers in Immunology, 2017)
The success of pregnancy is contingent on the maternal immune system recognizing and accommodating a growing semi-allogeneic fetus. Specialized subsets of lymphocytes capable of negative regulation are fundamental in this process, and include the regulatory T cells (Tregs) and potentially, regulatory B cells (Bregs). Most of our current understanding of the immune regulatory role of Bregs comes from studies in the fields of autoimmunity, transplantation tolerance, and cancer biology. Regulatory B cells control autoimmune diseases and can elicit graft tolerance by inhibiting the differentiation of effector T cells and dendritic cells, and activating Tregs. Furthermore, in cancer, Bregs are hijacked by neoplastic cells to promote tumorigenesis. Pregnancy therefore represents a condition that reconciles these fields – mechanisms must be in place to ensure maternal immunological tolerance throughout gravidity to allow the semi-allogeneic fetus to grow within. Thus, the mechanisms underlying Breg activities in autoimmune diseases, transplantation tolerance, and cancer may take place during pregnancy as well. In this review, we discuss the potential role of Bregs as guardians of pregnancy and propose an endocrine-modulated feedback loop highlighting the Breg-Treg-tolerogenic dendritic cells interface essential for the induction of maternal immune tolerance.